Interventions to Dispel Neuromyths in Educational Settings—A Review - Rousseau, Luc (Frontiers in Psychology, 2021)
Neuromyths are misconceptions about the brain and learning, for instance Tailoring instruction to students' preferred “learning styles” (e.g., visual, auditory, kinesthetic) promotes learning. Recent reviews indicate that the high prevalence of beliefs in neuromyths among educators did not decline over the past decade. Potential adverse effects of neuromyth beliefs on teaching practices prompted researchers to develop interventions to dispel these misconceptions in educational settings. This paper provides a critical review of current intervention approaches. The following questions are examined: Does neuroscience training protect against neuromyths? Are refutation-based interventions effective at dispelling neuromyths, and are corrective effects enduring in time? Why refutation-based interventions are not enough? Do reduced beliefs in neuromyths translate in the adoption of more evidence-based teaching practices? Are teacher professional development workshops and seminars on the neuroscience of learning effective at instilling neuroscience in the classroom? Challenges, issues, controversies, and research gaps in the field are highlighted, notably the so-called “backfire effect,” the social desirability bias, and the powerful intuitive thinking mode. Future directions are outlined.